Saint Francis and the Sultan: The Curious History of a Christian–Muslim Encounter By John Tolan (New York: Oxford University Press, 2009. 382 pages.) (American Journal of Islam and Society, 2012)
In August or September 1219 at the height of the Fifth Crusade, Francis ofAssisi audaciously set out to meet Sultan Malik al-Kâmil of Egypt. In SaintFrancis and the Sultan: The Curious History of a Christian–Muslim Encounter,historian John Tolan has produced a fascinating volume on this ratherstrange episode, an encounter that has captivated writers and painters for centuries.In an age when religion has lost much of its traditional power, however,the author wonders how much we can really know about the experience ofFrancis and al-Kâmil meeting each other “in a tent in an armed camp on thebanks of the Nile, during a truce in the midst of a bloody war” (p. 4). Insteadof trying to locate the real Francis and al-Kâmil in the fragments of history,Tolan asks why this particular has fascinated so many different artists. He answers,quite simply, that “for them, it was not merely a curiosity, or a footnoteto the history of a crusade which failed on the banks of the Nile. It was muchmore: an emblematic encounter or confrontation between East and West” (p.326). Whether it was seen as an encounter or a confrontation, in turn, depended in part on the historical, religious, and political context within which the givenartist was working. In this sense, the book reads more like a metahistory ofhow, why, and to what effect a particular historical episode has been depictedover the years.Given the focus on such a momentous encounter between East and West,Islam and Christianity, Muslim and Christian, as well as how it has been portrayedand understood, this book should be of particular interest to students ofChristian–Muslim relations and dialogue. It should also be of interest to peopleinterested in the construction of East/West and Muslim/Christian identity ...